2016
DOI: 10.1108/jsm-05-2014-0180
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationships between compassion at work, the evaluative perspective of positive work-related identity, service employee creativity, and job performance

Abstract: Purpose This study examines whether compassion at work increases service employees’ job performance. More specifically, the purpose of this study is to show the mechanism through which experienced compassion in an organization affects the job performance of service employees. Design/methodology/approach The employees from a department store in South Korea were surveyed using a self-administered instrument for data collection. Out of 550 questionnaires, a total of 309 usable questionnaires were obtained after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 61 publications
2
30
0
1
Order By: Relevance
“…194-195), which fits the purpose of our study. Past studies on compassion, such as Moon et al [16] and Hur et al [41], also used the same measurement providing empirical evidence of acceptable reliability and validity of the scale. Following Lilius et al [10], we measured the frequency of experienced compassion on the three aspects of work-(a) on the job, (b) from the supervisor, and (c) from coworkers, ranging from 1 = never to 5 = almost all the time.…”
Section: Compassionmentioning
confidence: 99%
See 1 more Smart Citation
“…194-195), which fits the purpose of our study. Past studies on compassion, such as Moon et al [16] and Hur et al [41], also used the same measurement providing empirical evidence of acceptable reliability and validity of the scale. Following Lilius et al [10], we measured the frequency of experienced compassion on the three aspects of work-(a) on the job, (b) from the supervisor, and (c) from coworkers, ranging from 1 = never to 5 = almost all the time.…”
Section: Compassionmentioning
confidence: 99%
“…Thus, we concluded Bednar et al [42] could capture the comprehensive picture of positive work-related identity. Although empirical studies on positive work-related identity are still limited, past studies, such as Moon et al [16] and Hur et al [41], also used the same measurement providing adequate evidence of its reliability and validity. Sample items read "As a member of this organization, I am a person of virtuous character" and "As a member of this organization, I exemplify virtuous qualities".…”
Section: Positive Work-related Identitymentioning
confidence: 99%
“…Their research on compassion has mainly relied on qualitative approaches, case studies to be specific, and Lilius et al (2008) have developed compassion scales to apply in their research. Conducting a study on compassion, Moon et al (2014) found the positive relationship between corporate social responsibility (CSR) and compassion, and Hur et al (2016) found the positive effects of compassion and positive work-related identity on performance variables. Empirical studies on compassion, qualitative or quantitative, have consistently increased since Lilius et al (2008) conducted an empirical study on the causal relationships among compassion, positive emotion, and affective commitment.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the relationship marketing research has become fragmented into areas such as relationship communication (e.g. Balaji, Roy and Wei, 2016), relationship dynamics (Harmeling, Palmatier, Houston, Arnold, and Samaha, 2015;Hollman, Jarvis and Bitner, 2015;Zhang Watson, Palmatier, and Dant, 2016), negative aspects of close relationship (Anderson and Jap, 2005) and the role of relationships in relation to other key issues such as service recovery (Hur, Moon and Jun, 2016) and service interactions (Martin, 2016). In conclusion, the relationship marketing research has moved to subareas, whereas many of its baseline ideas, such as inter-dependency between actors, are taken for granted in marketing.…”
Section: Introductionmentioning
confidence: 99%